CD63 expression on basophils in patients with allergy to beta-lactam antibiotics / Brenda Leecyous - Brenda , Leecyous (2017)
Immediate-type hypersensitivity reactions to beta-lactam antibiotics are an increasing clinical issue. However, diagnosis is challenging with little information from current available in vivo and in vitro tests. The gold standard test for diagnosis of drug allergy is the risky drug provocation test performed under close clinical supervision. In the current study, we aimed to study the expression of CD63 marker on basophil cells in patients with beta-lactam allergy, thus identify if this test can be useful in preventing misdiagnosis in these patients. We recruited 25 patients with suggestive clinical characteristics of allergy to beta-lactam antibiotics and 25 healthy controls. Skin Prick Test (SPT) using a panel of beta-lactam allergens consists of Penicilloyl-polylysine-Minor Determinant Mix (PPL-MDM), Amoxicillin and Clavulanic Acid were carried out in 24 patients. CD63 expression was determined by employing Basophil Activation Test (BAT) using Penicillin G, Penicillin V, Penicilloyl-polylysine (PPL), Minor Determinant Mix (MDM), Ampicillin and Amoxicillin, along with specific IgE quantification by Fluorescence Enzyme Immunoassay (FEIA) using Penicillin G, Penicillin V, Ampicillin and Amoxicillin in all participants. Of 24 patients, one patient was SPT-positive to Amoxicillin and in-house Ampicillin preparation. Two patients were BAT-positive and four patients were FEIA-positive. One patient showed consistent result in BAT and SPT while another patient showed consistent result in BAT and FEIA. We observed fair agreement between BAT and FEIA (Cohen Kappa Index=0.25). Although the agreement between CD63 expression in BAT and FEIA is fair, their diagnostic values are complementary. Despite good specificity, both tests demonstrated low sensitivity. BAT is particularly useful in patients with a clinical history of anaphylaxis and negative for FEIA, thus may avoid risky drug provocation test.